Resident impression management within feedback conversations: A qualitative study. Issue 2 (10th September 2020) - Huffman, Brandon M.; Hafferty, Frederic W.; Bhagra, Anjali; Leasure, Emily L.; Santivasi, Wil L.; Sawatsky, Adam P.
Abstract: Introduction: Medical education is moving to conceptualise feedback as a bidirectional learning conversation. Within this conversation, learners experience a tension between assessment and feedback. That perceived tension affects learners' outward performances. In this study, we aimed to characterise residents' experiences with this tension and its effect on learner authenticity within feedback conversations. Methods: In this constructivist grounded theory study, the authors were informed by Goffman's theory of impression management. During data analysis, Dweck's theory of mindset was adopted. The authors conducted semi‐structured interviews with 15 internal medicine residents. Data collection and analysis were conducted iteratively, using constant comparison to identify themes coinciding with impression management and mindset, ultimately developing a theoretical model to help explain residents' responses to tensions within feedback conversations. Results: Residents constantly felt 'scrutinized', and this affected their engagement in feedback conversations. They staged a performance within those conversations, linked to their underlying mindset: growth or fixed. Growth mindset was characterised by a focus on development as a physician and was associated with asking questions and seeking opportunities for growth. Fixed mindset was characterised by a focus on achieving a favourable evaluation and was associated with a hesitation to ask questions when faced with uncertainty and admit opportunities for growth, because they were concerned about impression management. Context influenced mindset and impression management. Residents adopted a fixed mindset and managed impressions when they perceived the permanence or consequences of evaluations within feedback. Residents adopted a growth mindset when they trusted the supervisor. Discussion: Residents assess the context of feedback conversations, altering the authenticity of their behaviours. Context, including the perceptions of formal assessment and relationships with supervisors, affected residents' mindset and impression management. Providing space for relationship‐building and clarifying the purpose and structure of assessment may be helpful in supporting effective learning conversations in graduate medical education. Abstract : Caught between learning and performance mindsets, Huffman et al. reveal that residents "front stage" a performance based mindset based on perceptions of formal assessment and their relationship with supervisors.